Design of a Web-Based E-Commerce Sales System for the Economic Empowerment of Tambak Fish Farmers - Siburian, Dian Prima Trendi; Hartiyani, Selvi Dwi; Wicaksono, Ardy; Gustina, Sapriani (IJID (International Journal on Informatics for Development), 2024)
This research addresses the economic challenges of fish farmers in Argomulyo Village, Cangkringan District, by developing a web-based e-commerce sales system. The primary issue identified is the limited market access experienced by these farmers. To address this, the study employs a qualitative research methodology using the Waterfall software development model and gathers data through observation, interviews, literature reviews, and questionnaires. The e-commerce platform aims to enhance economic opportunities for local fish farmers by providing a digital marketplace to overcome limited market access. Quantitative data was collected from 15 respondents using a questionnaire with 10 statements to evaluate the system. The analysis results show that the validity test (R Calculated > R Table) confirms all statements are valid, and reliability is tested with a Cronbach's Alpha of 0.958, exceeding the reference value of 0.6, indicating high reliability. The e-commerce system has proven effective in broadening market reach, boosting sales, and increasing farmers' income. The study results highlight the e-commerce system's positive impact on fish farmers' economic empowerment, demonstrating its potential to foster sustainable growth and market expansion in the digital era. This research provides valuable insights into the use of technology to enhance and advance the lives of farmers in rural communities.